Combating Increasing Chronic Non Communicable Diseases: The Need, Progress and Way Forward for Health Promoting Schools in South Africa - Dukhi, Natisha; Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
Epidemic increase in chronic non-communicable diseases (CNCDs) is resulting in immense challenges in developing countries such as South Africa. Previously misunderstood to affect only high-income countries, 80% deaths due to CNCDs occur in developing countries. This review article traces the path of health promotion in the Eastern Cape and South Africa while considering health promotion developments globally. An example is the Health- Promoting school initiative in 180 schools in the Eastern Cape Province based on the World Health Organization’s Health-Promoting School Initiative. Alma Ata’s holistic ‘health for all’ ideals, the WHO’s ‘Right to health’ along with South Africa’s Bill of Rights have remained important paper based progress. However partial implementation of certain policies and lack of implementation of most broad based health promotion is a major challenge in South Africa which has to be addressed urgently to reverse the advancing CNCD epidemic. Keeping healthy population healthy and training them to prevent CNCDs to the maximum possible extent is feasible by strategically focusing on Health promoting schools in South Africa. Community participation, women’s organizations and youth participation are critical in implementing Health promoting schools in South Africa while being supported by the intersect oral cooperation of key stakeholders in the Department of Health, Department of Education and community engagement services of Universities.
Keywords: Health promotion; schools; interventions; lifestyle; South Africa; Chronic Non Communicable Diseases